2021
DOI: 10.1016/j.ebiom.2021.103582
|View full text |Cite
|
Sign up to set email alerts
|

A novel fatty acid-binding protein 5 and 7 inhibitor ameliorates oligodendrocyte injury in multiple sclerosis mouse models

Abstract: Background: Multiple sclerosis (MS) is an autoimmune disease characterised by the demyelination of mature oligodendrocytes in the central nervous system. Recently, several studies have indicated the vital roles of fatty acid-binding proteins (FABPs) 5 and 7 in regulating the immune response. Methods: We assessed a novel FABP5/FABP7 inhibitor, FABP ligand 6 (MF 6), as a potential therapeutic for MS therapy. In vivo, we established MOG 35-55 -administered experimental autoimmune encephalomyelitis (EAE) mice as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…Apoe encodes a member of the apolipoprotein A1/A4/E family, and mutations in this gene are the strongest genetic risk factors for AD [47]. Fabp7 encodes a member of the fatty acid-binding protein family, which can bind to fatty acids, a crucial component of myelin [48; 49]. The BP analysis of DEGs revealed that downregulated DEGs were mainly related to protein synthesis, whereas upregulated DEGs were mainly concentrated in myelination-related pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Apoe encodes a member of the apolipoprotein A1/A4/E family, and mutations in this gene are the strongest genetic risk factors for AD [47]. Fabp7 encodes a member of the fatty acid-binding protein family, which can bind to fatty acids, a crucial component of myelin [48; 49]. The BP analysis of DEGs revealed that downregulated DEGs were mainly related to protein synthesis, whereas upregulated DEGs were mainly concentrated in myelination-related pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acid desaturase 2 (FADS2) single nucleotide polymorphisms (SNPs) rs174611 and rs174618 are both independent protective factors of MS incidence [46], and a higher level of serum fatty acid-binding protein (FABP4) associates with more severe symptoms evaluated by EDSS score [47]. A novel FABP5/7 inhibitor MF6 is proved to attenuate CNS demyelination in MS animal models by modulating inflammatory cytokines production of astrocytes and microglia, thus supporting oligodendrocytes survival by mitigating mitochondria oxidative stress [48].…”
Section: Intimate Relationship Between Fas and Msmentioning
confidence: 99%
“…An extensive metabolic investigation is warranted to examine the roles of each PA transporter in different glioma subtypes. Specific inhibitors targeting FABP5 and FAT/CD36 have been developed and successfully tested in other disease models, which can be applied to glioma research [ 40 , 41 ].…”
Section: Palmitic Acid Uptake and Incorporation Into The Sphingolipid...mentioning
confidence: 99%